The Correlation Between Quality of Digital Services in Mobile JKN Application And BPJS Patient Satisfaction at Kebomas Health Center Indicates A Significant Correlation - Saputra, Rizma Dwi Ady; Suminar, Ervi (INNOVATION RESEARCH JOURNAL, 2025)
BPJS Kesehatan July 2024 participants are 31,770 people, while Mobile JKN users are 184 people. Based on a preliminary study on August 5, 2024 with 10 respondents, 6 were not satisfied with the use of Mobile JKN because there was no KIA poly, registration was not readable in the Puskesmas system. But 4 was satisfied because it was easy and received medical services, without carrying a physical BPJS card. The research uses a quantitative approach. The design of this study is a cross-sectional study. The population in this study is 184. This study uses the purposive sampling method ̧ sampling with certain criteria for a total of 128 samples. The instrument uses a questionnaire. Data analysis uses a spearman rank correlation test. The result most (68.0%) stated that the quality of the digital services of the Mobile JKN application was good as many as 87 patients. Almost all (73.4%) expressed satisfaction with 97 patients. The results of the spearman rank p value test analysis were 0.00 < α value 0.05. There is a relationship between the quality of digital services of the Mobile JKN application and BPJS patient satisfaction at the 2024 Kebomas Gresik Health Center. It is hoped that the quality of digital services can be improved so that the use and assessment of patients is even higher. Keywords: Digital services, patient satisfaction, Mobile JKN.